FOREIGN DIRECT INVESTMENT ANALYSIS OF INDONESIA 1992 – 2022 - Hifdani Amal Abdika; Muhamad Farizi; Ahmad Taufiq Rohman; Achmad Jufri (FEB - Universitas Lampung, 2024)
Foreign direct investment (FDI) plays an important role in the economic development of a country, including Indonesia. This research uses descriptive qualitative and quantitative methods with secondary data in the form of open data from the World Bank and the Central Statistics Agency to analyze the development of FDI in Indonesia from 1992 to 2022. Foreign investment fluctuates, influenced by economic and political crises, changes in infrastructure, and challenges. Although Indonesia has successfully recovered from the economic crisis of the late 1990s, the COVID-19 pandemic had a significant impact in 2020. The government's response and stimulus measures have helped maintain economic recovery. The synergy between the Indonesian government and foreign investors can boost national economic growth. This study provides an in-depth understanding of the dynamics of FDI in Indonesia and provides a basis for improving policies and strategic direction for sustainable economic development. Despite existing challenges, Indonesia continues to attract investor interest from various countries and sectors, with the potential to increase equitable investment allocation in the region.